Integrating advanced neural network architectures with privacy enhanced encryption for secure and intelligent healthcare analytics - C. Ramesh Babu Durai; S. Dhanasekaran; M. Jamuna Rani; Sindhu Chandra Sekharan (Scientific Reports)
Abstract Healthcare data protection in our mutually connected era has emerged as an issue of serious concern with private patient information, which has been exposed more often due to data violations and cyber-attacks. Network structures CNN and LSTM as part of privacy-based encryption method. Research presents neurosis, a new structure, which combines CNN-LSTM architecture with privacy-secured encryption to provide safe healthcare analytics. Depending on the Kaggle healthcare dataset, the model receives an accuracy of 98.73%, which is better than the current functioning. “NeuroShield” includes characteristic-based access control (ABAC), Advanced Encryption Standard (AES), Multi-Factor Authentication (MFA) and differential privacy-based optimizations that provide strong protection. To increase the interpretation, AI (XAI) is used on the basis of size, making health experts capable of understanding model decisions. Detailed evaluation accepts the performance of structure in maintaining privacy through providing high-demonstration analysis for healthcare data protection. Organized testing and comparative analysis suggest that neuroshield not only improves data security, but also provides excellent accuracy with better performing results in healthcare analytics.